2020
DOI: 10.4317/medoral.23353
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of clinical outcomes and histomorphometric findings in alveolar ridge augmentation procedures with allogeneic bone block grafts: A systematic review and meta-analysis

Abstract: Background: This systematic literature review aimed to evaluate the efficacy of allogeneic bone blocks for ridge augmentation by assessing block survival rates and subsequent implant survival, including post-surgical complications and histomorphometric analysis. Material and Methods: An electronic and manual search among references, was conducted up to April 2019 by two independent authors. Inclusion criteria were: human clinical trials in which the outcomes of allogeneic bone block grafts were evaluated by me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 36 publications
6
12
0
Order By: Relevance
“…It should be noted that the highest values were found with allogeneic bone rings, with a 97.93% survival rate after a 12.70-month follow-up. These findings agree with previous systematic reviews analyzing implant survival rates after GBR and bone block grafting, which report survival rates of between 97% and 100% [ 5 7 , 30 ].…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…It should be noted that the highest values were found with allogeneic bone rings, with a 97.93% survival rate after a 12.70-month follow-up. These findings agree with previous systematic reviews analyzing implant survival rates after GBR and bone block grafting, which report survival rates of between 97% and 100% [ 5 7 , 30 ].…”
Section: Discussionsupporting
confidence: 93%
“…The mean survival rate obtained in the present review was 97.26%; with 100% for allogeneic bone rings and 95.04% for autogenous bone rings. These outcomes are similar to other vertical ridge augmentation procedures [ 7 , 30 , 33 ].…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…The analysis of this work used histomorphometry and immunohistochemistry, these methodologies are widely used to assess cell tissue components involved in the osseointegration and bone remodeling process. [13][14][15][16] The results of the present study showed that the synthetic nano-HA/ß-TCP mixture biomaterial used to fill calvarial bone defects in a rat model induced a better cell response than deproteinized bovine bone mineral (DBBM). Nano-HA/ß-TCP mixture showed larger percentages of stained areas with Masson's trichrome, PAS, MMP-9, and TNF-α than DBBM biomaterial.…”
Section: Discussionmentioning
confidence: 75%
“…Although autogenous bone has been described by some authors as the ‘ gold standard ’ for bone augmentation procedures due to its osteogenic, osteoinductive, and osteoconductive properties, it suffers several disadvantages, such as higher morbidity, the need for a donor site, and the limited quantity of bone available [ 37 ]. Besides, autogenous bone block grafting presents a range of complications derived from the technique, occurring in 30–50% of cases [ 38 , 39 , 40 ].…”
Section: Discussionmentioning
confidence: 99%